Electrochemical synthesis of 5-trifluoroethyl dihydrobenzimidazo[2, 1-a] isoquinolines from pendent unactivated alkenes via radical relay. (12th April 2023) - Lv, Yi; Dai, Jia-Ying; Zhao, Zi-Xin; Liu, Jia; Li, Zhi-Wei; Lu, Cui-Hong; Zhang, Yue-Fei; Liu, Wei-Dong; Li, Jiang-Sheng
Graphical abstract: Abstract: An electrochemical radical relay method for direct access to 5-(2, 2, 2-trifluoro)ethyl dihydrobenzimidazo[2, 1- a ]isoquinoline derivatives from benzimidazole-tethered pendent unactivated alkenes in an undivided cell is developed. This method is applicable to Langlois reagent and difluoro analog, tolerates a wide range of functional groups and activated sp 3 CH bonds, and obviates the need for external oxidants. The so-formed heterocycles display good fungicidal activities, especially against Botrytis.